Pro Apache Tomcat 6 - Moodie, Matthew; Mittal, Kunal (Apress : Imprint: Apress, 2007)
Pro Apache Tomcat 6 is ideal for Tomcat administrators and others who want to configure Tomcat. It covers only Tomcat 6 and doesn't get bogged down trying to overexplain tasks from each older version of the server. The book examines the entire installation, including file system, database, and web server, and provides you with security and performance tips. Author Matthew Moodie describes configuration files, as well as administration features like security, auto-deployment, remote deployment, and data sources. He gets right to the point and teaches you to use Tomcat without wasting time on Java or JSP introductions or excess discussion of JSP and Java code.